Pengaruh Pengalaman Pemasaran terhadap Loyalitas Pelanggan Rumah Kecantikan dr Rina dengan Kepuasaan sebagai Variabel Intervening - Santika, Dinda; Harahap, Hastuti Handayani; Sarwoto, Sarwoto (Economic Development Progress, 2022)
Marketing theories become the basic theory, especially the theory of consumer behavior. The aim of the study is to show answers to the research hypothesis: marketing experience influences customer satisfaction with a T-statistic value of 19.593 and customer loyalty with a T-statistic value of 2.676. Customer loyalty is influenced by customer satisfaction, the value of the T-statistic is equal to 3.245 and customer satisfaction is the intervening variable between the effect of marketing experience on customer loyalty with a coefficient value of 0.4122. The research was conducted on 97 respondents as well as being the research sample. Data processing using SPSS 25.0 software